Niche segregation between Arctic char ( Salvelinus alpinus ) and brown trout ( Salmo trutta ): an experimental study of mechanisms - Jansen, Peder A; Slettvold, Henning; Finstad, Anders G; Langeland, Arnfinn (Canadian Journal of Fisheries and Aquatic Sciences, 2002)
Interactive competition has been suggested to be an important mechanism by which brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus) segregate into benthic vs. pelagic niches. According to the interactive competition hypotheses, Arctic char and brown trout should have the same preference for prey. We tested this by studying foraging performance when char and trout were offered small pelagic Daphnia longispina and (or) large epibenthic Gammarus lacustris in 10-min foraging experiments with solitary fish and with fish competing pairwise. There were obvious behavioural differences between char and trout. Trout were profoundly more aggressive than char. In comparison, char chose small pelagic daphnids and were superior daphnid foragers. Trout chose large epibenthic gammarids and were superior gammarid foragers. When competing, char and trout segregated such that rate of feeding on the chosen prey type was similar to solitary foraging fish, whereas rate of feeding on the alternative prey type was close to zero. We suggest that the observed selective differences in foraging behaviour, choice of prey, and feeding rates play an important role in niche segregation between Arctic char and brown trout. Hence, our results conform more closely with selective processes, rather than interactive processes, as the founding mechanisms for such segregation.